PENGARUH TINGKAT PENGANGGURAN, PERTUMBUHAN PENDUDUK, DAN IPM TERHADAP TINGKAT KEMISKINAN DI PROVINSI JAWA TENGAH - Dana Putra, Marshell Bahreiza; Furqon, Imahda Khoiri (LPPM Universitas Bina Bangsa, 2024)
One of the socioeconomic problems that every region is responsible for is poverty. Poverty is a social problem that has existed for a long time and is difficult to eradicate until now. So what can affect poverty and how to influence it. The majority of developing countries, including Indonesia, experience poverty. This research is quantitative research, with data analysis techniques, namely multiple linear regression analysis. The data used in this study are secondary data sourced from bps. The results showed that the unemployment rate has a negative effect on poverty, population growth has a negative effect on poverty, and HDI has a negative effect on poverty. Simultaneously, the three variables have no effect and are not significant on poverty